Towards Strengthening Technology Culture amongst MSEs:: Evidence from a Field Study in Bangalore, India - Rajakumar, J. (Journal of Comparative International Management, 2011)
The Micro and Small Enterprises (MSEs) contribute a great deal in income and employment generation in India. The MSEs competitiveness is often marred by the level of technology they adopt. Realizing the vital role played by these units in the economy, previous Government of India provided tacit support to encourage them in adopting new technology. This shifted away from the hitherto approach of viewing the technology as the mere generators of employment. While state intervention could harness their growth, the forms of intervention require a careful examination of technology culture amongst MSEs. To explore firms’ tendencies in this regard, a field level investigation was conducted covering a few auto component manufacturing firms based in Bangalore. Availability of skilled labor and ease of finance were found to be the major constraints to technology acquisition and upgradation. While there are a plethora of government sponsored schemes implemented through other formal credit market channels, there are obstacles faced by the units in accessing those credit facilities. Based on the findings, the paper outlines some state interventions that may enhance technology acquisition and upgradation processes amongst the MSEs